Enhancing Cost and Security of Arabic SMS Messages over Mobile Phone Network - Abdullah Abdullah (Al-Rafidain Journal of Computer Sciences and Mathematics, 2009)
This paper investigates a novel algorithm for compressing and encrypting Arabic short text messages (SMS messages). Short text messages are used in cellular networks. Compression is required for saving the transmission energy or to use bandwidth in an efficient manner in addition to save the user money while the end-to-end effective encryption is required for security providence. This work succeeded to overcome small size limitation of the SMS message by changing Arabic characters coding from Unicode to Base64 coding scheme and developing a runt version of lossless Huffman coding scheme. Examples are shown where the application of the text compressor for short message services offering more than three times the capacity compared to a standard message.